Answer:
(n ≤ -3) ∪ (-1 ≤ n)
Explanation:
I like to "unfold" the absolute value expression by copying the right-side expression to the left side (with the same comparison symbol) and negating its value. I do it this way because I find it easier to work the problem "all at once".
-1 ≥ n +2 ≥ 1
Obviously, -1 ≥ 1 is not true, which means the solution to this inequality will be disjoint sections of the number line. A compound inequality of this nature is generally interpreted to mean the AND of the two inequalities. So, technically, this is an incorrect step. I choose to overlook that, and consider the expression to represent the two inequalities ...
-1 ≥ n +2 . . . OR
n +2 ≥ 1
Subtracting 2 from the above compound inequality gives ...
-3 ≥ n ≥ -1
So, the solution is ...
(n ≤ -3) ∪ (-1 ≤ n)
_____
Further explanation
The inequality symbol negates its content if that content is negative. So, the expression ...
|n+2| ≥ 1
means ...
±(n +2) ≥ 1
This resolves to two cases:
n +2 ≥ 1
and
-(n +2) ≥ 1
The latter case is equivalent to ...
n +2 ≤ -1
which can also be written as ...
-1 ≥ n +2
A more technically correct solution process would identify the two cases and work them separately.
__
In the graph, the red shading (with the solid edge) shows the solution with respect to the numbers on the x-axis. If you were to graph this on a number line, you would put solid dots at -3 and -1, and shade the line to their left and right, respectively. The blue curve shows the absolute value, and the green line shows y=1, so you can see that the shaded areas correspond to the absolute value being greater than or equal to 1.